The Lyricism of W.O. Mitchell’s Who Has Seen the Wind - Gingell-Beckman, S. A. (Studies in Canadian Literature, 1981)
The interests of most critics who have commented on the lyricism of W.O. Mitchell’s Who Has Seen the Wind have tended to be primarily thematic rather than stylistic, so that observations about style have either gone undocumented or been supported simply by quoting a "poetic passage" from the novel without any attempt at analyzing the style to account for lyric effect. Yet, those defining features of the lyric mode that combine to create the requisite, single, unified impression – the subjective, personal, and imaginative view of a subject, the intense, even ecstatic, emotion evoked in the lyrical writer by the subject, and the careful attention paid to the music in the sounds of the words by which the subject is expressed – all these features of lyricism are clearly identifiable in the most memorable passages of Who Has Seen the Wind.